Investigating the Effect of Psychographic and Demographic Variables on the Purchase of Sports Products (Case Study of Green Purchase of Sports Goods) - Mohammad Saeid Kiani; leila Nazari; Shahab Bahrami (Research in Sport Management and Marketing)
Purpose: This study investigated the effective of factors (demographic-social variables and mental grapy variables) on the behavior of purchase green.Methods: The objective of the research applied and in terms of the research methodology is descriptive and correlational. The statistical population included all the physical education students of Kermanshah province who will refer to the sports shop. The number of sample size were 196 people have been selected randomly to sampling method.Results: Data of this research through the standard questionnaire was achieved by distributing among the students. Content validity, construct validity used in this study and they were acceptable for this research, and reliability of questionnaire with Cronbach alpha 0/86percent was approved.Conclusion: To analyze the data, SPSS and Amos software was used. After analysis test showed that social variables - population on consumer behavior environmental awareness there is not significant positive effects. Also Mentalgerapy variables of environmental awareness on consumer behavior, consumer behavior on purchase intention green, green shopping behavior and ultimately affect purchase intention green on green behavior.